Expression of human BRCA1Δ17-19 alternative splicing variant with a truncated BRCT domain in MCF-7 cells results in impaired assembly of DNA repair complexes and aberrant DNA damage response - Sevcik, Jan; Falk, Martin; Macurek, Libor; Kleiblova, Petra; Lhota, Filip; Hojny, Jan; Stefancikova, Lenka; Janatova, Marketa; Bartek, Jiri; Stribrna, Jana; Hodny, Zdenek; Jezkova, Lucie; et al. (Cellular signalling, 2013)
Alternative pre-mRNA splicing is a fundamental post-transcriptional regulatory mechanism. Cancer-specific misregulation of the splicing process may lead to formation of irregular alternative splicing variants (ASVs) with a potentially negative impact on cellular homeostasis. Alternative splicing of BRCA1 pre-mRNA can give rise to BRCA1 protein isoforms that possess dramatically altered biological activities compared with full-length wild-type BRCA1. During the screening of high-risk breast cancer (BC) families we ascertained numerous BRCA1 ASVs, however, their clinical significance for BC development is largely unknown. In this study, we examined the influence of the BRCA1Δ17-19 ASV, which lacks a portion of the BRCT domain, on DNA repair capacity using human MCF-7 BC cell clones with stably modified BRCA1 expression. Our results show that overexpression of BRCA1Δ17-19 impairs homologous recombination repair (sensitizes cells to mitomycin C), delays repair of ionizing radiation-induced DNA damage and dynamics of the ionizing radiation-induced foci (IRIF) formation, and undermines also the non-homologous end joining repair (NHEJ) activity. Mechanistically, BRCA1Δ17-19 cannot interact with the partner proteins Abraxas and CtIP, thus preventing interactions known to be critical for processing of DNA lesions. We propose that the observed inability of BRCA1Δ17-19 to functionally replace wtBRCA1 in repair of DNA double-strand breaks (DDSB) reflects impaired capacity to form the BRCA1-A and -C repair complexes. Our findings indicate that expression of BRCA1Δ17-19 may negatively influence genome stability by reducing the DDSB repair velocity, thereby contributing to enhanced probability of cancer development in the affected families.
Keywords: poškození DNA; endodeoxyribonukleasy; Radiation, Ionizing; protein BRCA1; DNA Damage; Protein Structure, Tertiary; terciární struktura proteinů; ionizující záření; jaderné proteiny; MFC-7 buňky; MCF-7 Cells; Carrier Proteins; DNA Repair; oprava DNA; lidé; alternativní sestřih; Humans; Endodeoxyribonucleases; BRCA1 Protein; Alternative Splicing; Nuclear Proteins; transportní proteiny